2002
DOI: 10.1046/j.1365-313x.2002.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of plastid DNA replication origins in tobacco by targeted inactivation

Abstract: SummarySequences described as chloroplast DNA replication origins were analysed in vivo by creating deletion and insertion mutants via plastid transformation in tobacco. Deletion of the described oriA sequence, which is located within the intron of the trnI gene, resulted in heteroplastomic transformants, when the selection marker was inserted within the intron. Removal of the complete intron sequence together with the oriA sequence, however, yielded homoplastomic transformants of normal phenotype, in which wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…In vitro replication analysis has revealed that the minimal sequences required for activity of single-ori ctDNA templates in tobacco is 82 bp for oriA and 243 bp for oriB (Kunnimalayaan and Nielsen, 1997b). There are conflicting reports on the effect of deletions of chloroplast oris (Muhlbauer et al, 2002;Kunnimalayaan and Nielsen, 1997b;Lu et al, 1996;Lugo et al, 2004). It is quite possible that disruption of an ori in vivo is not lethal if another mechanism can take over.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro replication analysis has revealed that the minimal sequences required for activity of single-ori ctDNA templates in tobacco is 82 bp for oriA and 243 bp for oriB (Kunnimalayaan and Nielsen, 1997b). There are conflicting reports on the effect of deletions of chloroplast oris (Muhlbauer et al, 2002;Kunnimalayaan and Nielsen, 1997b;Lu et al, 1996;Lugo et al, 2004). It is quite possible that disruption of an ori in vivo is not lethal if another mechanism can take over.…”
Section: Discussionmentioning
confidence: 99%
“…oriB1 is in the coding region of the essential gene ycf1, whose function is still not known (Drescher et al 2000). oriB2 is in the reading frame orf 350 and-unlike oriB1-it can be deleted from all plastome copies (Mü hlbauer et al 2002). It is not clear, if these differences between the oriBs reflect biological differences, e.g.…”
Section: Identity Of Fragment Endsmentioning
confidence: 99%
“…In addition, in suspension cultures of N. tabacum a different replication origin-also in the inverted repeats-was found (Takeda et al 1992). It was possible to delete both oriA sequences from all plastome copies and-in different lines-also one of the oriB sequences was completely removed (Mü hlbauer et al 2002). ptDNA replication in N. tabacum might therefore be possible from only one of the oriB elements.…”
Section: Introductionmentioning
confidence: 99%
“…OriA/B-independent replication of the spa19 PS1 genome is conceptually consistent with other examples. For example, deletion of oriA in tobacco chloroplasts had no obvious effect, but both copies of oriB could not be deleted (Muhlbauer et al 2002) and indeed, tobacco cpDNA appears to have multiple replication origins (Scharff and Koop 2007). We also note that OriA could not by itself promote maintenance of an extrachromosomal element in Chlamydomonas chloroplasts (Suzuki et al 1997).…”
Section: Discussionmentioning
confidence: 73%